MYC deregulation sensitizes cancer cells to N-myristoyltransferase inhibition - Gregor A. Lueg; James Zhang; Monica Faronato; Andrii Gorelik; Wouter W. Kallemeijn; Francesco Falciani; Josephine Walton; Jack W. Houghton; Silvia Vannini; Evon Poon; Barbara M. Costa; Roberto Solari; et al. (Cell Reports)
Summary: Human N-myristoyltransferases (NMTs) catalyze N-terminal protein N-myristoylation and are promising targets in cancer, with an emerging mechanistic rationale for targeted therapy. Here, we screened 245 cancer cell lines against IMP-1320, a potent NMT inhibitor (NMTi), and conducted pathway-level analyses to identify that deregulated MYC increases cancer cell sensitivity to NMTis. Proteomics on detergent-enriched membrane fractions in MYC or MYCN-deregulated cancer cell models revealed that cell death is associated at least in part with loss of membrane association of mitochondrial respiratory complex I. This is concurrent with loss of myristoylation and degradation of the complex I assembly factor NDUFAF4, and induction of mitochondrial dysfunction, driven by MYC or MYCN-deregulation. NMTis eliminated or suppressed MYC- and MYCN-driven tumors in vivo without overt toxicity, suggesting that this constitutive co-translational protein modification can be targeted in MYC-driven cancers.